Accountting Study of Non-Profit Entities Based on Sak Etap Isak 35 - Rengku, Jeffry Otniel; Lintong, Jerry Sonny (Future Science, 2022)
The Evangelical Christian Church in Minahasa is a very developed church, and has succeeded in developing its service to the community with various forms of service, such as establishing schools, help the underprivileged congregation through the coffers of love, cooperatives, free medical treatment and so on. The success of the church in presenting clear and transparent financial reporting, becomes a measure of the success of every program that has been planned. In addition, church administrators can easily make accountability to God and church members. Accountability increases the confidence of the congregation, so that they do not hesitate to make donations, as well as transparency reduces misunderstandings or suspicions in the church, including conflicts and divisions that should become one in Christ and the church can continue to improve its services for the glory of God. This study aims to determine the financial management of GMIM, by conducting studies and comparing the management among church organizations, evaluating the financial process into financial statements. The method used is a qualitative method by reviewing transactions that occur at any time, the notes used by each treasurer which are then compiled by Congregation Assembly Working Agency in Financial Statements according to activities. Analysis of the data used is to explain, describe the method of financial management of all cash receipts transactions starting from financial data to become information during the reporting period.